2017
DOI: 10.1007/s00221-017-5099-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of robotic training depends on motor task characteristics

Abstract: Previous research suggests that the effectiveness of robotic training depends on the motor task to be learned. However, it is still an open question which specific task's characteristics influence the efficacy of error-modulating training strategies. Motor tasks can be classified based on the time characteristics of the task, in particular the task's duration (discrete vs. continuous). Continuous tasks require movements without distinct beginning or end. Discrete tasks require fast movements that include well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 55 publications
2
32
1
Order By: Relevance
“…Although previous research has shown that motivation can be modulated through robotic assistance (Duarte and Reinkensmeyer, 2015;Marchal-Crespo et al, 2017b;Bernardoni et al, 2019), we did not find significant differences between training strategies in any subscale of the Intrinsic Motivation Inventory. The lack of significant differences could be due to the generally high overall interest/enjoyment and effort/importance (i.e., ceiling effect) and the high variability observed across participants.…”
Section: No Differences In Motivation Across Training Strategiescontrasting
confidence: 99%
“…Although previous research has shown that motivation can be modulated through robotic assistance (Duarte and Reinkensmeyer, 2015;Marchal-Crespo et al, 2017b;Bernardoni et al, 2019), we did not find significant differences between training strategies in any subscale of the Intrinsic Motivation Inventory. The lack of significant differences could be due to the generally high overall interest/enjoyment and effort/importance (i.e., ceiling effect) and the high variability observed across participants.…”
Section: No Differences In Motivation Across Training Strategiescontrasting
confidence: 99%
“…Here, only a brief summary is given for completeness. Similar haptic disturbance (Marchal-Crespo et al, 2017a) and error modulating controllers (Marchal-Crespo et al, 2017c) were developed to perform motor learning experiments with ARMin, a 7 degree-of-freedom (DoF) robotic exoskeleton for upper limb rehabilitation. The haptic controllers employed in the present experiment, however, were developed in joint coordinates and were not based on the end-effector trajectories.…”
Section: Methodsmentioning
confidence: 99%
“…We employed six statements (Table 1) from the well-established Intrinsic Motivation Inventory (IMI, Ryan, 1982). The IMI has been successfully employed in several motor learning experiments to assess intrinsic motivation (Duarte and Reinkensmeyer, 2015; Marchal-Crespo et al, 2017c). The full questionnaire assesses seven motivational subscales (with a total of 45 questions).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that error amplification (Abdollahi et al 2014 ; Bouchard et al 2015 ; Emken and Reinkensmeyer 2005 ; Patton and Mussa-Ivaldi 2004 ) or haptic guidance (Bouchard et al 2015 , 2016 ; Marchal-Crespo et al 2013 ) training techniques allow improvement in subjects’ performance of the learned task. In healthy individuals, direct comparison of the effectiveness of these two techniques on promoting learning showed that for various upper or lower limb tasks, EA training using either force fields (Marchal-Crespo et al 2014 , 2017b ) or visual distortions (van Asseldonk et al 2009 ) led to higher learning rate than HG training. However, in a previous study of ours, using a timing-based pinball-like task (identical to the one of the current study), we found that both EA and HG training techniques were beneficial to improving subjects’ timing performance.…”
Section: Introductionmentioning
confidence: 99%